Eigenmobilities in background electrolytes for capillary zone electrophoresis: IV. Computer program PeakMaster - Jaros, Michal; Hruska, Vlastimil; Stedrý, Milan; Zusková, Iva; Gas, Bohuslav (Electrophoresis, 2004)
We are introducing a computer implementation of the mathematical model of zone electrophoresis (CZE) described in Stedry, M., Jaros, M., Hruska, V., Gas, B., Electrophoresis 2004, 25, 3071-3079 program PeakMaster. The computer model calculates eigenmobilities, which are the eigenvalues of the matrix tied to the linearized continuity equations, and which are responsible for the presence of system eigenzones (system zones, system peaks). The model also calculates other parameters of the background electrolyte (BGE)-pH, conductivity, buffer capacity, ionic strength, etc., and parameters of the separated analytes--effective mobility, transfer ratio, molar conductivity detection response, and relative velocity slope. This allows the assessment of the indirect detection, conductivity detection and peak broadening (peak distortion) due to electromigration dispersion. The computer model requires the input of the BGE composition, the list of analytes to be separated, and the system instrumental configuration. The output parameters of the model are directly comparable with experiments; the model also simulates electropherograms in a user-friendly way. We demonstrate a successful application of PeakMaster for inspection of BGEs having no stationary injection zone.
Keywords: Electrolytes; elektrolyty; elektroforéza kapilární; Electrophoresis, Capillary; Software; Osmolar Concentration; počítačová simulace; Computer Simulation; osmolární koncentrace; software